The impact of capital gains and dividend payout ratio on stock trading volume: evidence from indonesian infrastructure companies - Dewi Dian Emor; Billy Ivan Tansuria (Jurnal Konseling dan Pendidikan, 2025)
This study investigates the influence of capital gains and the dividend payout ratio on stock trading volume among Indonesian infrastructure companies. Using panel data from 47 firms listed on the Indonesia Stock Exchange during the 2020–2023 period and applying multiple linear regression analysis, the findings reveal that both capital gains and dividend payout ratios have a statistically significant positive effect on trading volume. Notably, the dividend payout ratio demonstrates a stronger influence than capital gains, indicating the importance of dividend policy in shaping investor behavior. These results suggest that consistent and transparent dividend policies can enhance market liquidity and investor confidence in the infrastructure sector, offering valuable implications for corporate financial strategies, regulatory considerations, and investment decision-making.